Post-liquefaction Handling of Community Housing in Central Sulawesi - Andi Pasinringi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The three major disasters on 28 September 2018 that occurred in Central Sulawesi gave the local government the opportunity to prove how to better rebuild post-disaster settlements and shelters. The researcher tries to see whether knowledge of post-disaster reconstruction can be applied according to the policies that have been decided. The approach taken starts with local government regulations supported by local documents as a literature review. Qualitative data were collected through observation, document analysis, and interviews with the Regional Disaster Management Agency and affected community leaders. The government's efforts to relocate affected communities to permanent and temporary housing are still ongoing, even after two years of the disaster. Data collection and socialization have been carried out, but the central budget is inadequate, so that the fulfillment of new developments is carried out at certain points.